Mutualismo ou tentativa de sindicalismo católico? : A propósito do movimento dos círculos católicos de operários (1898-1910) - Gonçalves, Eduardo Cordeiro (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The present article analyses the activity of the Catholic circles with regards to the labour issue, focusing on the Catholic Labour Circle of Porto (Círculo Católico de Operários do Porto) as a central object of this study, in the context of the publication of the Rerum Novarum encyclic.